The First High-Throughput Sequencing-Based Study of Viruses Infecting Solanaceous Crops in Kosovo Reveals Multiple Infections in Peppers by Six Plant Viruses - Burim Ismajli; Zsuzsanna N. Galbács; András Péter Takács; Éva Várallyay (Plants)
High-throughput sequencing (HTS) was employed for the first time to investigate plant viruses infecting solanaceous crops, including potato (Solanum tuberosum), tomato (Solanum lycopersicum), and pepper (Capsicum annuum), in Kosovo. Leaf samples showing virus-like symptoms were collected from various regions during the summer of 2023. Based on ribodepleted RNA sequencing and bioinformatics analysis, six viruses were identified: cucumber mosaic virus, broad bean wilt virus 2 (BBWV2), potato virus Y, pepper cryptic virus 2 (PCV2), bell pepper endornavirus (BPEV), and ranunculus white mottle virus. BBWV2, PCV2, and BPEV are reported for the first time in the Balkan region. Virus presence was validated using RT-PCR. Phylogenetic analyses revealed that the identified viral strains did not cluster according to their hosts and geographical origins. CMV and BBWV2 variants exhibited reassortment events, indicating possible local evolution or novel virus introductions. This research highlights the widespread occurrence of mixed infections in pepper plants and highlights the need for additional research into the virus transmission dynamics and potential reservoir hosts. These findings emphasize the need for continuous surveillance and integrated plant protection strategies to mitigate the impacts of viral infections on pepper and other economically important crops in Kosovo.